Static and dynamic functional connectivity analysis of cerebrovascular reactivity: An fMRI study. Issue 6 (27th April 2020) - Lewis, Noah; Lu, Hanzhang; Liu, Peiying; Hou, Xirui; Damaraju, Eswar; Iraji, Armin; Calhoun, Vince
Abstract: Background: Cerebrovascular reactivity (CVR) is an important aspect of brain function, and as such it is important to understand relationship between CVR and functional connectivity. Methods: This research studied the role of CVR, or the brain's ability to react to vasoactive stimuli on brain functional connectivity by scanning subjects with blood‐oxygenation‐level‐dependent (BOLD) functional magnetic resonance imaging (fMRI) while they periodically inhale room air and a CO 2‐enriched gas mixture. We developed a new metric to measure the effect of CVR on each intrinsic connectivity network (ICN), which contrasts to voxel‐wise CVR. We also studied the changes in whole‐brain connectivity patterns using both static functional network connectivity (sFNC) and dynamic FNC (dFNC). Results: We found that network connectivity is generally weaker during vascular dilation, which is supported by previous research. The dFNC analysis revealed that participants did not return to the pre‐CO 2 inhalation state, suggesting that one‐minute periods of room‐air inhalation is not enough for the CO 2 effect to fully dissipate. Conclusions: Cerebrovascular reactivity is one tool that the cerebrovascular system uses to ensure the constant, finely‐tuned flow of oxygen to function properly. Understanding the relationship between CVR and brain dynamism can provide unique information about cerebrovascular diseases and general brain function. We observed that CVR has a wide, but consistent relationship to connectivity patterns between functional networks. Abstract : We analyzed the effect of CO2 on both static and dynamic functional network connectivity. In addition, we measure the cerebrovascular reactivity of connectivity networks.